Purchase Intention Determinants and Beneficiary Satisfaction: Evidence from Kerala Agricultural Development Society (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Beneficiary satisfaction and purchase intention are critical indicators of the effectiveness and sustainability of agricultural development organisations. Purchase intention reflects beneficiaries’ willingness to continue purchasing products, while satisfaction arises from their overall evaluation of product quality, pricing, and service experiences. The Kerala Agricultural Development Society (KADS) plays a significant role in supporting agricultural development in Kerala by ensuring fair prices for farm produce, promoting organic and eco-friendly agricultural practices, and reducing the influence of intermediaries.This study examines the key determinants influencing purchase intention and beneficiary satisfaction among KADS beneficiaries. Using empirical evidence collected from beneficiaries across Kerala, the study analyses the relationship between organisational initiatives, perceived value, satisfaction, and purchase intention. The findings highlight that fair pricing mechanisms, product quality, and trust in KADS significantly influence beneficiary satisfaction, which in turn positively affects purchase intention. The study provides practical insights for strengthening beneficiary-oriented strategies and enhancing the effectiveness of agricultural development programmes implemented by KADS.